2003
DOI: 10.1128/aac.47.11.3458-3463.2003
|View full text |Cite
|
Sign up to set email alerts
|

Quinine Pharmacokinetic-Pharmacodynamic Relationships in Uncomplicated Falciparum Malaria

Abstract: The relationships between the pharmacokinetic properties of quinine during a 7-day treatment course and the therapeutic response were studied in 30 adult patients with uncomplicated falciparum malaria monitored for >28 days. All patients received a 7-day oral quinine regimen either alone (n ‫؍‬ 22) or in combination with rifampin (n ‫؍‬ 8). The median fever clearance time was 58.5 h, and the mean ؎ standard deviation parasite clearance time was 73 ؎ 24 h. After recovery, six patients had recrudescences of Plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
50
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 15 publications
4
50
0
Order By: Relevance
“…Because clindamycin is a slowly acting drug, clindamycin is a candidate for combination treatment with fast-acting drugs, such as quinine. [12][13][14][15][16][17] Clindamycin, usually combined with quinine, has been used extensively in South America and also proved effective in adults and children with acute malaria. The efficacy of clindamycin plus quinine for children has not been evaluated in the South east Asian region, where the most drug resistant Plasmodium falciparum strains are found.…”
Section: Discussionmentioning
confidence: 99%
“…Because clindamycin is a slowly acting drug, clindamycin is a candidate for combination treatment with fast-acting drugs, such as quinine. [12][13][14][15][16][17] Clindamycin, usually combined with quinine, has been used extensively in South America and also proved effective in adults and children with acute malaria. The efficacy of clindamycin plus quinine for children has not been evaluated in the South east Asian region, where the most drug resistant Plasmodium falciparum strains are found.…”
Section: Discussionmentioning
confidence: 99%
“…This is essential for the success of the treatment once a marked interpersonal and interracial difference in quinine disposition have been demonstrated 3,4,5 . Therefore, this work was done to elucidate this relationship in an endemic area of Amazon region, in a prospective clinical treatment trial.…”
mentioning
confidence: 99%
“…This result demonstrated that quinine do not concentrate in red blood cell of Brazilian children and demonstrates an absence of interracial differences in agreement with previous studies that show the ratio between the plasma and red blood cell quinine concentrations varied from 0.2 to 2.3. The variability in this relation could be of therapeutic relevance, once the concentration of quinine in plasma and red blood cell must remain above levels which inhibit parasite multiplication throughout the course of treatment to eradicate the infection because there is a higher probability that a resistant strain will emerge if the drug is present at a sub therapeutic concentration 3,4,7,8 .…”
mentioning
confidence: 99%
See 2 more Smart Citations